(untitled) (ModaPalavra e-periódico, 2021)
The purpose of the article is to analyze the representation of old age in the work of Brazilian designer Ronaldo Fraga. Methodologically, it consists of a theoretical reflection on old age and fashion from three stylist shows at São Paulo Fashion Week (2009, 2017, 2018), in which the old man appeared as a model. It is clear that Fraga proposes to break the negative representations of old age, such as ugliness, social isolation, inactivity, etc. On the contrary, the parades showed possible subversions of these representations, in which the old people are invited by Fraga to assume his symbols of aging and to find beauty in them.